PRINCIPLES OF SURGICAL TREATMENT IN PATIENTS WITH OSTEOARTHRITIS OF THE FIRST METATARSOPHALANGEAL JOINT - M. R. Nurmukhametov (Научно-практическая ревматология, 2018)
At present, there is no general approach to choosing surgical tactics for hallux rigidus. Many surgical procedures are used to treat osteoarthritis (OA) of the first metatarsophalangeal joint (FMPJ), which are relevant at different stages of the disease. Nevertheless, this fact also suggests that all proposed methods have one or other disadvantages. At the same time, FMPJ arthrodesis that relieves pain and is functionally inferior to joint-sparing surgery remains the gold standard. However, due to the fact that not only persons over the age of 50 years, but also younger patients often suffer from FMPJ OA, the most non-damaging option of joint-sparing surgery is cheilectomy with chondroplasty of the FMPJ, which allows restoration of painless joint motions, thus sparing the anatomy of the foot. Chondroplasty using the authologous matrix-induced chondrogenesis (AMIC®) technique for knee, hip, and ankle cartilage defects is described. There are no reports on FMPJ chondroplasty with the AMIC method in either Russian or foreign literature.